Thymoquinone loaded calcium alginate and polyvinyl alcohol carrier inhibits the 7, 12‐dimethylbenz[a]anthracene‐induced hamster oral cancer via the down‐regulation of PI3K/AKT/mTOR signaling pathways. Issue 3 (17th October 2020) - Pu, Yumei; Hu, Shiqi; Chen, Yongfeng; Zhang, Qian; Xia, Chengwan; Deng, Han; Wang, Yuxin; Hu, Qingang
Abstract: Oral cancer is a multifactorial cancer that affects millions of peoples worldwide. The current exploration aimed to evaluate the mechanisms that thymoquinone nanoencapsulated carrier and its effects on 7, 12‐Dimethylbenz[a]anthracene (DMBA) stimulated hamster buccal pouch cancer in Syrian hamster model. Nanocarrier was characterized by SEM, TEM, FTIR analysis. The incidence of tumor, and biochemicals makers was studied through standard methods. The mRNA expression level of inflammatory markers NF‐κBp50, NF‐κBp65, and PI3K/AKT/mTOR markers in the buccal tissues of control and experimental animals were investigated through RT‐PCR analysis. In thymoquinone (TQ) loaded calcium alginate and polyvinyl alcohol carrier (TQ/Ca‐alg‐PVA) no squamous cell carcinogenesis developed and others moderate dysplasia revealed differentiated form of hyperplasia and keratosis. In biochemical analyses with DMBA + TQ/Ca‐alg‐PVA (20 mg/kg bw) orally administered hamsters showed restored the antioxidants, detoxification, xenobiotic metabolising enzymes in DMBA induced plasma and oral tissues of hamsters. Further, mRNA expression level of NF‐κBp50/p65 and PI3K/AKT/mTOR were upregulated in the DMBA alone painted hamster. In contrast, these expressions were down regulated in orally TQ/Ca‐alg‐PVA treated experimental animals. This ability more eligible to deregulate the inflammatory and PI3K/AKT/mTOR signaling pathway that proved it suppresses anti‐invasion/metastasis activity during hamster buccal pouch carcinogenesis. From this study, we recommended that TQ/Ca‐alg‐PVA has documented as effective chemopreventive agents, in further many molecular machineries need to study. Abstract : The gene expression levels of IL‐6, pJAK‐2, JAK‐2, and STAT‐3 were analyzed in all experimental groups. Data are depicted as mean ± SD of triplicate measurements. Statistical significant level was calculated via ANOVA subsequently DMRT study; note: "*" P < .05 when compared with control group and "**" P < .01 when compared with DMBA induced group.